1.
a)(4-2x)-(x+3)=(x-5)+-3-x)
b)(3-2x)+(3x+4)=-(3-2x)+(5x+4)
c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
2.
a)(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x+6)
d)6(x+1+3(2-x)=2(2x-1)-(4-x)
pilne daje naj.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T23:02:19+01:00
1.
a)
(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3-4+3
-3x=-9
x=3

b)
(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6
x=1

c)
(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x=4+6+5+7-8
7x=14
x=2

d)
-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=-1-5-7+4+4
-8x=-5
x=5/8

2.
a)
(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-4-7-3+4+5
-3x=-5
x=1⅔

b)
(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=3-7-4+3+4
x=-1

c)
(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x+6)
4x-5+x-7-2x+8=-3x+4-x-6
4x+x-2x+3x+x=4-6+5+7-8
7x=2
x=2/7

d)
6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18
x=9